Factors associated with Institutional delivery in Boricha district of Sidama zone, southern Ethiopia - Tafese Tadele Gudura; Alemu Tamiso Debiso; Tariku Tadele Gudura (International Journal of Public Health Science (IJPHS), 2014)
Every year, 40 million women give birth at home without the help of askilled birth attendant. In 2011, 287,000 women died during pregnancy or childbirth. Almost all these deaths occur in developing countries where mothers and children lack access to basic health care. Reports showed the low utilization of health facility for delivery service in Ethiopia. This study aimed to determine the utilization and factors influencing institutional delivery. Community based cross sectional study was conducted from January to February 2013/14 in Boricha District of Southern Ethiopia among mothers who gave birth in the last 1 year. Multistage sampling techniques were used to collect data from 546 mothers. Taking in to account place of birth for the last child, only 4.9% women gave birth in a health facility. Women’s education level (AOR=4.4 (95% CI=1.36-14.33)), timing of firstANC visit (AOR= .03 (95% CI=0.004 - 0.205)), women’s advice to deliver in a health facility during ANC (AOR = 31.15 (95% CI=2.02-479.52)), women’s knowledge of birth related complications (AOR= 12.4 (95% CI=2.67-57.16)) and decision making power (AOR=0.2 (95% CI=0.060.82)) showed significant association with institutionional delivery. Institutional delivery in the study area was found to be very low. Raising awareness on institutional delivery to maximize delivery service utilization and strengthening provision of education and counseling to deliver in health facility during antenatal care visits at individual and community level should be given due emphasis.